Alcohol induction of liver nuclear ethanol and N-nitrosodimethylamine metabolism to reactive metabolites - Diaz Gomez, Maria Isabel (2002)
In previous studies from our laboratory we reported the presence in highly purified liver nuclei, free of contamination with other organelles, of an ethanol metabolizing system (NEMS) able to lead to acetaldehyde and 1-hydroxyethyl free radicals (1HEt). In the present study we tested whether this NEMS is inducible by chronic alcohol administration to rats and whether these nuclei also have increased ability to bioactivate N-nitrosodimethylamine (NDMA). Sprague Dawley male rats (125-150g) were fed with a nutritionally adequate liquid diet containing alcohol to provide 36% of total energy (standard Lieber-De Carli rat diet), for 28 days. Controls received an isocaloric diet without alcohol. Animals were sacrificed, livers were excised and microsomes and purified nuclear fractions were prepared. Both microsomes and nuclei from treated animals had significantly increased ability compared to controls, to biotransform ethanol to acetaldehyde using NADPH as cofactor under an air atmosphere. Both organelles also exhibited significantly increased capacity compared to controls, to bioactivate NDMA to formaldehyde and to reactive metabolites that bind covalently to proteins. Nuclear preparations from control animals were also able to metabolize NDMA to formaldehyde and reactive metabolites. Results indicate that liver nuclei may have a CYP2E1 able to bioactivate both NDMA and EtOH and that these processes are being induced by chronic alcohol drinking. The bioactivation of these xenobiotics to reactive metabolites in the neighborhood of nuclear proteins and DNA might have significant toxicological implications.